2001
DOI: 10.1046/j.1463-1318.2001.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional recurrence in patients with anastomotic leakage after anterior resection for rectal carcinoma

Abstract: Anastomotic leakage after anterior resection for rectal carcinoma is a risk factor for locoregional recurrence and decreases cancer-related survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
1
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 15 publications
(21 reference statements)
1
53
1
6
Order By: Relevance
“…Determining the role of anastomotic leakage in long-term oncological outcome has important clinical pertinence as knowledge of an association may impact consideration for further treatment. However, the effects of anastomotic leakage on local recurrence and long-term oncologic outcomes are controversial [4][5][6][7][8][9][10][11]. Contradictory findings could have been reported because of inconsistent leakage definitions or variability in administered treatments [12].…”
Section: Introductionmentioning
confidence: 99%
“…Determining the role of anastomotic leakage in long-term oncological outcome has important clinical pertinence as knowledge of an association may impact consideration for further treatment. However, the effects of anastomotic leakage on local recurrence and long-term oncologic outcomes are controversial [4][5][6][7][8][9][10][11]. Contradictory findings could have been reported because of inconsistent leakage definitions or variability in administered treatments [12].…”
Section: Introductionmentioning
confidence: 99%
“…4,25,26 However, later studies suggested that anastomotic leakage results in increased local recurrence 9-13 and a decrease in cancer-specific survival. [9][10][11] Given the severity of a staple line failure, the concept of buttressing to strengthen the staple line is attractive. Currently, buttressing options include sealant materials, such as fibrin glue, and the incorporation of synthetic or biologic materials into the staple line.…”
Section: Discussionmentioning
confidence: 99%
“…The general incidence of anastomotic leakage varies, although is still thought to average approximately 10 percent. [1][2][3][4][5][6] Anastomotic leakage is influenced by numerous factors and is associated with a significant increase in 30-day mortality, 7,8 increased rates of local recurrence of cancer, [9][10][11][12][13] and is the most common cause of anastomotic strictures. 14 Despite the excellent results achieved with the use of mechanical stapling devices, staple lines are not immune to failure.…”
mentioning
confidence: 99%
“…Aus eigenen Untersuchungen wissen wir, dass Anastomoseninsuffizienzen, vermutlich durch eine lokale Implantation von Tumorzellen, das Auftreten von Lokalrezidiven begünsti-gen können [11]. Die ohnehin äußerst hohen Kosten einer Anastomoseninsuffizienz würden somit durch die Kosten des Lokalrezidivs weiter in die Höhe getrieben.…”
Section: Kostenersparnis Durch Qualitätsorientierte Arbeitunclassified